Ambiências bioecológicas sustentáveis na práxis pedagógica (auto)formativa do professor do CEI casa da criança - Zanatta, Aline Aparecida Hofstetter (2022)
His dissertation is part of Research Line Two, Pedagogical Management and Educational Contexts, of the Professional Master's Degree in Public Policy and Educational Management, Postgraduate Program in Public Policy and Educational Management at the Federal University of Santa Maria. Its theme is “Sustainable Bioecological Ambiences as a (self) formative pedagogical praxis for teachers at CEI Child House”. The different ambiences of a school allow relationships to be built through experiences and cultural diversity, which is revealed in the plural context of an educational institution, being experienced, observed and recorded. It is in listening and interacting that subjects carry out the most incredible transformations, to which they suggest great learning. As a problem, we are guided by the following question: How is a proposal for continuing education configured through an Investigative-Formative Group that contemplates sustainable and (self) training bioecological environments articulated in the proposal of the CEI Child House and in the emerging demands from everyday? As a general objective of the research, we seek to systematize the emerging demands of the daily life of the CEI Child House for studies in the field of (self) teacher formative and sustainable bioecological ambiences and propose the construction of a Formative Investigative Group as a proposal for continuing education. The research is characterized as a qualitative study, following the research-training perspective, having as a study model the Bioecological Theory of Human Development by Urie Bronfenbrenner and the Concept of Sustainable Bioecological Ambience, by Maciel and Avinio (2019). This Dissertation qualified the processes experienced by the group of teachers from CEI Child House in their context, times and spaces, as shown by the results, in images and text.